2021
DOI: 10.3390/biomedicines9080897
|View full text |Cite
|
Sign up to set email alerts
|

Co-Players in Chronic Pain: Neuroinflammation and the Tryptophan-Kynurenine Metabolic Pathway

Abstract: Chronic pain is an unpleasant sensory and emotional experience that persists or recurs more than three months and may extend beyond the expected time of healing. Recently, nociplastic pain has been introduced as a descriptor of the mechanism of pain, which is due to the disturbance of neural processing without actual or potential tissue damage, appearing to replace a concept of psychogenic pain. An interdisciplinary task force of the International Association for the Study of Pain (IASP) compiled a systematic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 134 publications
0
59
0
1
Order By: Relevance
“…They found that angry faces evoked greater responses in highly anxious participants compared to angry faces with an averted gaze, while the response to fearful faces increased with anxiety for both direct and averted gaze conditions. Recent studies untangled the pathophysiology underlying anxiety disorders: experimental and preclinical evidence revealed that anxiety disorders are determined by the abnormal neural processing of threat-related stimuli, which is mediated by the cyclic AMP (cAMP)-protein kinase A (PKA) pathway [90][91][92]. Additionally, the downregulation of the regulatory subunit of PKA within the amygdala can lead to an augmentation of anxiety-like behavior, resulting in changes in amygdala activation in response to a gaze [93].…”
Section: Conjoint Processing Of Emotional Expressions and Gaze Direct...mentioning
confidence: 99%
“…They found that angry faces evoked greater responses in highly anxious participants compared to angry faces with an averted gaze, while the response to fearful faces increased with anxiety for both direct and averted gaze conditions. Recent studies untangled the pathophysiology underlying anxiety disorders: experimental and preclinical evidence revealed that anxiety disorders are determined by the abnormal neural processing of threat-related stimuli, which is mediated by the cyclic AMP (cAMP)-protein kinase A (PKA) pathway [90][91][92]. Additionally, the downregulation of the regulatory subunit of PKA within the amygdala can lead to an augmentation of anxiety-like behavior, resulting in changes in amygdala activation in response to a gaze [93].…”
Section: Conjoint Processing Of Emotional Expressions and Gaze Direct...mentioning
confidence: 99%
“…Despite the lack of studies showing the role of the kynurenine metabolites in COVID-19 pain, many studies have shown its relationship with neuropathic pain and other painful conditions ( Rojewska et al, 2016 ; Rojewska et al, 2018 ; Staats Pires et al, 2020 ; Jovanovic et al, 2020 ; Ciapała et al, 2021 ; Tanaka et al, 2021 ). Some metabolites can act as immunomodulators depending on the dose or the situation, perpetuating low-grade inflammation ( Tanaka et al, 2020 ).…”
Section: Kynurenine Pathway and Covid-19mentioning
confidence: 99%
“…The biogenesis of pain can be underlined by nociceptic, neuropathic, and neuroplastic mechanisms. The kynurenine pathway of L-Trp metabolism may be involved in pain pathogenesis, and the most likely effect associated with this involvement is neuroinflammation (reviewed in [43]). The most common form of pain is nociceptive pain, which is caused by a structural dysfunction, including tissue damage occurring, e.g., in bone fractures (reviewed in [44]).…”
Section: The Gut-brain Axismentioning
confidence: 99%